Developing English Language Materials for Health and Business Students at Institut Kesehatan dan Bisnis St. Fatimah Mamuju - Susiandari, Ariawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
English for Specific Purposes (ESP) has become an essential component of higher education, particularly for students majoring in health and business fields. This research aims to develop English learning materials tailored to the academic and professional needs of students at Institut Kesehatan dan Bisnis St. Fatimah Mamuju. The study applied the Research and Development (R&D) design using the Borg and Gall (1983) model, adapted into four stages: needs analysis, material design, expert validation, and try-out. Data were collected through questionnaires, interviews, and classroom observations involving 60 students and 5 lecturers from both health and business programs. The findings revealed that students required practical English competencies such as medical terminology, patient communication, business correspondence, and presentation skills. The developed materials consisted of thematic modules integrating reading, speaking, writing, and listening exercises relevant to healthcare and business contexts. Expert validation indicated that the materials were feasible, user-friendly, and contextually appropriate. Furthermore, students reported improved motivation and confidence in using English for their specific academic and workplace needs. The study concludes that ESP-based materials are effective in bridging the gap between general English proficiency and professional requirements in health and business disciplines.